DISOLVED OXYGEN PERFORMANCE IN DEGRADATION OF TOTAL PETROLEUM HYDROCARBONS BY EX SITE ACTIVATED SLUDGE - Abubakar Tuhuloula (Konversi, 2020)
Contamination of soil by the activities of exploration, production and disposal of oil waste into the environment causes serious damage to the environmental ecosystem, the target of processing by the activated sludge as a model for remediation of petroleum contaminated site. Optimization of oxygen supply becomes special attention in aerobic bioprocess for optimizing the growth of microorganisms to degrade total petroleum hydrocarbons. Thus, the study was focused on determining the performance of dissolved oxygen in degradation of total petroleum hydrocarbons by ex situ activated sludge. The research used biological methods (bioremediation), with the ratio of contaminated soil to water was 20:80%(w/v) and a soil size 40/50 mesh.  The degradation process was carried out with 15% and 20% (v/v) activated sludge put into the bioreactor slurry with a capacity of 4 liters and stirring was 90 rpm at a temperature of 30oC as well as aeration and nutrient injection into the bioreactor. TPH analysis was measured by the gravimetric method. The results obtained showed that the performance of dissolved oxygen increased well in the bioreactor slurry at 15% (v/v) and 20% (v/v) activated sludge concentrations was 3.31–8.57 mg/L and 3.5–8.21 mg/L respectively, which had an impact on the level of TPH degradation, namely from 18,000 µg/g to 2870 µg/g and 18,000 µg/g to 1970 µg/g during the 49 days remediation period. In general, activated sludge shows good performance throughout the remediation period.